Genetic variability and relationship of phenolic contents, antioxidant capacity and grain yield components of selected coloured rice accessions - Mohd Sarif, Hamidah (2019)
Rice is one of the most important food crops and a primary source of calories for more than half of the world’s population. Nowadays, there is increasing demand for the coloured rice due to growing knowledge of health benefits. Coloured rice is one of the alternative healthy foods since it contains high antioxidant, phenolic compounds, and other nutrients that have significant benefit on human health. In this study, genetic diversity was evaluated among 32 coloured rice accessions. Rice accessions were obtained from Rice Genebank, Malaysian Agricultural Research and Development Institute (MARDI) and were planted at the field for multiplications, morphological and yield components assessment. The evaluation was carried out in a randomized complete block design (RCBD) with three replications. The analysis of variance results showed that all the agro-morphological characteristics, yield and yield components, grain quality, and antioxidant properties were significant differences among the accessions. Correlation analysis revealed that phenolic content positively high correlated with plant height, leaf area, heading days, number of tillers, thousand grain weight, dehulled grain width, amylose content and gel consistency. Most of the characteristics studied had high heritability values (>70%) except for numbers of tillers (40.72%), alkaline spreading value (40.68%), broken rice percentage (22.98%) and head rice recovery (7.74%). These indicated that the characters with high heritability values (>70%) were highly influenced by genetic factor than environmental factors in their phenotypic expression. The coloured rice accessions had broad genetic divergence and high heritability values will be given high priority in the selection for successful improvement of rice grain quality. Correlation analysis showed that phenolic content was positively significant correlated with all the morphological traits and yield components. The total antioxidant capacities (TAC) for all the coloured rice accessions were ranged from 12.10 to 34.90 μM/100g total equivalent antioxidant capacity (TEAC). The highest of TAC content was identified in accession DNJ 128 (34.90 μM/100g TEAC). For molecular diversity study, out of 59 simple sequence repeats (SSR) markers used, 34 markers showed polymorphism among the coloured rice accessions. The polymorphic information content (PIC) ranged from 0.86 (RM137) to 0.97 (RM400) with an average 0.92 which indicated that SSR markers used in this study were effective to reveal the polymorphic among the rice accessions. Cluster analysis using unweighted pair group method with arithmetic mean (UPGMA) showed that all the coloured rice accessions were grouped into four clusters. From this study, six coloured rice accessions namely, YTM 15, Pulut Merah 3, Padi Randau, Ringan Bawang, DNJ 128 and DV 107 produced high yield with good grain quality and high antioxidant capacity were selected for future rice breeding program.